Problems and Strategies in Comics Translation - Larasati, Shinta Dwikanti; Rasikawati, Ira (International Dialogues on Education Journal, 2022)
Comics are illustrated stories that have been an alternative entertainment for many people of all ages. They can be fictional stories such as myths, legends, fairy tales, science fiction, and folklore. There are two types of comics: printed comics and digital comics. Many comics are translated from the source language to the target language. The translation process should ensure that the target text language is parallel with the source text language. Occasionally there are inaccurate translations, and the original message that the author wants to convey to the reader cannot be delivered. Due to the multimodality of comics, their translation often involves more complex processes compared to that of other text types. This literature review aimed to identify what problems exist in comics translation and what solutions had been suggested to overcome the problems. The primary goals were to synthesize the existing literature describing patterns of problems and strategies in translating comics. The data was collected from thirty research reports on the translation of comics in which the source language was either English or Indonesian. The review found five categories of problems with the two most frequent strategies suggested to overcome the problems.